THE TECHNIQUES AND WAYS OF USING VIDEOS IN EL CLASSROOMS - Narbekova , Ra’no Usmanovna (Educational Research in Universal Sciences, 2023)
The article deals with the growing tendency to integrate different technologies into language teaching that exists today. Besides, the article has tackled the issues of appropriate video material selection and analysis of the activities that effectively utilizing videos in teaching.